Exploring The Postmodern Multiple Subjectivity In Selected Works Of Malaysian Prose Fiction In English - Yakin, Haryasindra Mohd. (2023)
The focus of this study is to examine the representation of the postmodern multiple subjectivity in the works of a few contemporary Malaysian writers. The concept of the postmodern multiple subjectivity comprises of two other concepts which are the concept of the double (Freud, 1919) and the concept of the protean self by Lifton (1993). The writers that comprise the corpus of this study include Karim Raslan, Dina Zaman, Tash Aw, Zen Cho, Sharmilla Ganesan and Angeline Woon to explore the dynamism of the postmodern self in responding to the challenges brought about by the social and cultural changes that have taken place due to globalisation, transnationalism and diaspora. This research also endeavours to study a group of vibrant and contemporary Malaysian writers whose mode of writing reflects a break away from the nationalistic fervour, local and communal sentiments shown by Malaysian writers in the years preceding the 21st century. These new writers approach issues of the self and identities in a much broader sense, mirroring a postmodern outlook in their works as a result of the influences of technological developments, sophisticated interconnectivity of communications and free movements of people across the globe.